PENDEKATAN INTERKULTURAL SEBAGAI MODEL MISIONAL: SEBUAH UPAYA UNTUK MEREKONSTRUKSI MISI DI ABAD XXI - Talan, Yesri Esau (Universitas Sanata Dharma, 2023)
The integration of mission and culture are two things that cannot be separated. Because when an evangelist preaches the gospel, he will be confronted with people who live in a certain cultural context. This turned out to be a problem in carrying out the Great Manda of the Lord Jesus. Because if an evangelist does not pay attention to the cultural values adopted by a particular community and contextualize the gospel, there will be negative syncretism that has an impact on spiritual life. Or conversely, if an evangelist realizes that the Bible and a culture that has been polluted with sin are in two different poles and tries to transform the wrong cultural values, when it is contextualized in the context of a particular society, the gospel will definitely be rejected. That is why the purpose of this research is to reconstruct the mission of the XXI century so as not to fall into the same problem by offering an intercultural approach as a mission bridge. This study uses qualitative research methods, namely the results obtained are described. In addition to the books used as material for analysis, interviews, observations and documentation are also the main materials in analyzing. The results of this study indicate that the intercultural approach is a biblical missionary approach because this approach is able to bridge the Bible to a context without assimilation and rejection of the people who live in their local culture